2017
DOI: 10.1038/srep41216
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D and 2D quantitative shear wave elastography (SWE) to differentiate between benign and malignant breast masses

Abstract: As breast cancer tissues are stiffer than normal tissues, shear wave elastography (SWE) can locally quantify tissue stiffness and provide histological information. Moreover, tissue stiffness can be observed on three-dimensional (3D) colour-coded elasticity maps. Our objective was to evaluate the diagnostic performances of quantitative features in differentiating breast masses by two-dimensional (2D) and 3D SWE. Two hundred ten consecutive women with 210 breast masses were examined with B-mode ultrasound (US) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…Maximum elasticity max on 3D SWE was significantly higher than that on 2D SWE, which is concordant with the finding in previous literature on the breast. 14,15 One possible reason is that 3D SWE provides a more comprehensive evaluation of the nodule than 2D SWE and thus has a higher chance of finding the stiffest region within the nodule. For example, the stiffest region may be detected in the coronal plane of 3D SWE, which is hard to obtain with 2D SWE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Maximum elasticity max on 3D SWE was significantly higher than that on 2D SWE, which is concordant with the finding in previous literature on the breast. 14,15 One possible reason is that 3D SWE provides a more comprehensive evaluation of the nodule than 2D SWE and thus has a higher chance of finding the stiffest region within the nodule. For example, the stiffest region may be detected in the coronal plane of 3D SWE, which is hard to obtain with 2D SWE.…”
Section: Discussionmentioning
confidence: 99%
“…Bhatia et al reported that when E_SD was used as a surrogate indicator of heterogeneity, malignant thyroid nodules showed significantly higher heterogeneity than benign nodules. Tian et al found that E_SD showed better diagnostic accuracy compared with E_max on 3D SWE for differentiating malignant from benign breast lesions. Therefore, for 3D SWE, E_SD, rather than E_max or E_mean, should be applied for differentiation between malignant and benign thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Putting a region of interest (ROI) in the area being investigated provides quantitative information about tissue elasticity in kilopascals or meter per second [11]. At present, SWE technology has been widely and successfully used in diagnosis of various diseases such as diseases in gland, vessel wall and superficial organ [12,13]. It is also used to detection of portal hypertension in cirrhosis which can use to reflect the liver stiffness with comparable or better success rate and accuracy as compared with TE [14] and can be used to diagnose patients with or without clinical significant portal hypertension [15].…”
Section: Introductionmentioning
confidence: 99%